(untitled) (Journal of the College of Basic Education, 2022)
Highlights the importance of research in finding solutions to regulatory management activities and sporting events, school through the use of management principles so as to achieve Achievements good considering that the administration is one of the necessities needed by the human in all life activities, including the athlete, the research problem Vtthdd through the weakness of the administrative and regulatory framework for the work of supervisors Departmentof sports activity and Scout and moderators supervision department specialist, educational and lack of interest in teacher / physical education teacher currency in earnest in the performance of his duties as required, and the objectives of the research is to instill educational concepts in the hearts of students and instill the love of individual games and the difference among students through the element of competition, and the use of a researcher at the This approach is descriptive style screening for most schools breeding Baghdad Karkh /2 , where the researcher on the division of the geographical area to 6 breakers as conducted tournaments difference for the schools Cutters six-run school and one for each breaker in each game, and the most important conclusions is that the nature of the business sections of activity Scout Sports and lacked precision in the selection of elements representing teams of Physical Education The recommendationsthe need to follow the adoption of the teachers and teachers of physical education management principles in their daily work because it will give them a chance to work and programming come out with positive results.